Diversity and inclusion in clinical trials: Evolution throughout the development of an mRNA COVID-19 vaccine - Jameka Hill; Diane Montross; Melanie Ivarsson (Frontiers Media S.A., 2023)
Despite the importance of equitable representation in clinical trials, disparities persist with racial and ethnic minorities remaining largely underrepresented in trial populations. During the coronavirus disease 2019 (COVID-19) pandemic, wherein disease disproportionately affected racial and ethnic minority groups, the necessity for diverse and inclusive representation in clinical trials has been further highlighted. Considering the urgent need for a safe and efficacious vaccine, COVID-19 vaccine clinical trials faced marked challenges in rapidly enrolling participants without forgoing diverse representation. In this perspective, we summarize Moderna's approach toward achieving equitable representation in mRNA-1273 COVID-19 vaccine clinical trials, including the COVID-19 efficacy (COVE) study, a large, randomized, controlled, phase 3 trial of mRNA-1273 safety and efficacy in adults. We describe the dynamics of enrollment diversity throughout the COVE trial and the need for continuous, efficient monitoring and rapid pivoting from initial approaches to address early challenges. Insights gained from our varied and evolved initiatives provide key learnings toward achieving equitable representation in clinical trials, including establishing and listening to a Diversity and Inclusion Advisory Committee, repeatedly engaging with key stakeholders on the necessity for diverse representation, creating and disseminating inclusive materials to all trial participants, establishing methods to raise awareness for interested participants, and enhancing transparency with trial participants to build trust. This work shows that diversity and inclusion in clinical trials can be attained even in the most extreme circumstances and highlights the importance of efforts toward building trust and empowering racial and ethnic minorities with the knowledge to make informed medical treatment decisions.